CONTINUOUS HOLTER MONITORING OF PATIENTS WITH CARDIOVASCULAR DISEASES IN ORAL SURGERY - Hristo Daskalov; Lyudmila Vladimirova-Kitova; F. Nikolov; E. Sarachev (Peytchinski Publishing, 2011)
Introduction. Pain control and anxiety management are important aspects of modern dental treatment. Although many local anesthetics and anesthesia techniques have so far been studied, there is still no clarity as to what anesthetic should be used in cardiovascularly compromised patients. This anesthetic and its dosage should be very carefully chosen to achieve optimal effective pain control; the possible side effects occurring mainly in morbidly compromised patients should also be well studied.Methods. The aim of this study was to study the effect of vasoconstrictors on local anesthetics in 18 patients with heart diseases. The study contingent was recruited from the patients visiting often their general dental practitioners and diagnosed with the following heart diseases: Heart failure (after 6 months); ischemic heart disease, including mild angina pectoris. Articaine was used as local anesthetic. Results. The ST segment on the ECG was used to detect myocardial ischemia and to study the effect of the administered local anesthesia.Conclusion. The study results suggest that pain control in a cardiovascularly compromised patient subjected to oral surgery should be carried out only after thorough analysis is conducted of the specific condition and current status of the patient. Additional hematological tests shoud be done to enable the dentist to build a viable treatment plan.